2004
DOI: 10.2114/jpa.23.225
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise in Cool, Control and Hot Environments on Cardioprotective HSP70 Induction

Abstract: A number of environmental and metabolic stimuli rapidly induce the expression of several highly conserved proteins such as heat shock proteins (HSPs) or stress proteins. The purpose of this study was to investigate the effects of a single bout of submaximal exercise in varying ambient temperatures on cardiac and skeletal muscle. Adult male Sprague-Dawley rats were randomly placed in one of three ambient temperature groups; control (23°C), hot (41°C) and cool (11°C). Each exercise bout consisted of treadmill ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…2007). Mammalian Hsps has induced by various ambient temperatures or environments in vivo (Fujimori et al 1994;Kim et al 2004). Transportation is thought to be very stressful due to exposure of the animals to unfavorable environments.…”
Section: Discussionmentioning
confidence: 99%
“…2007). Mammalian Hsps has induced by various ambient temperatures or environments in vivo (Fujimori et al 1994;Kim et al 2004). Transportation is thought to be very stressful due to exposure of the animals to unfavorable environments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they revealed that exercise in a cold environment could provide protection against the same insult without increasing cardiac HSPs (HSP10, HSP40, HSP60, HSP70, HSP90). This indicates that the rise in body temperature during exercise is an essential component of the exercise-induced HSP overexpression [90][91][92]. However, Harris and Starnes [91] reported that the limitation of the rise in core temperature during endurance training sessions (room temperature at 4-8°C) with consequent lack of effect on myocardial HSP accumulation, abolished the cardioprotection observed when room temperature during exercise training is maintained neutral (23°C), thus resulting in HSP70 overexpression.…”
Section: Heat Shock Proteins and Exercise-induced Cardioprotectionmentioning
confidence: 99%
“…Heat shock was the first known stressor to induce an increase in cellular HSP content (Ritossa 1962, Tissieres et al 1974) and both in vitro (Maglara et al 2003) and in vivo (Oishi et al 2002(Oishi et al , 2003 heating protocols have been shown to induce an increased HSP content in C 2 C 12 skeletal muscle myotubes and rodent muscle, respectively. Furthermore, the exercise-induced production of HSP70 in soleus muscle of rodents is enhanced when exercise is performed under elevated ambient temperatures, an effect attributed to the significantly higher body temperatures in these conditions (Kim et al 2004).…”
mentioning
confidence: 99%